Phytoremediation of Heavy Metals Contaminated Soil in Artisanal Gold Mining at Selogiri, Wonogiri District, Central Java, Indonesia - Bambang Suryo Madyo Pranoto; Wawan Budianta (Journal of Applied Geology, 2021)
Artisanal gold mining (ASGM) is commonly found in Indonesia, particularly in Wonogiri District, Central Java. One of the impacts of ASGM activity is soil contamination influence by mining waste. The objective of this study to investigate the potential use of Amaranthus spinosus L. and Jatropha curcas for remediation of Pb and As in contaminated soil. Phytoremediation experiment was conducted by using Amaranthus spinosus L. and Jatropha curcas and evaluate the effectiveness of both plants as a hyperaccumulator. The result shows that the higher Pb and As concentration was found in roots rather than shoots in both plants, however, the use of Jatropha curcas seems more effective on reducing Pb and As concentrations more than Amaranthus spinosus L in both shoots and roots. Generally, the use of both hyperaccumulator plants was more effective in Pb remediation compared to As. This phytoremediation experiment revealed that the use of both hyperaccumulator plants reduces the concentrations of Pb and As in contaminated soil, which of the critical point leading to the entry of Pb and As into the food chain.